Muscle stem cells: what’s new in orthopedics? - Biz, Carlo; Crimi, Alberto; Fantoni, Ilaria; Pozzuoli, Assunta; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Adult stem cells were studied as a source of potentially useful development for tissue engineering and repair techniques. The aim of this review is to clarify the actual and possible uses of muscle stem cells in orthopedics. Methods: A selection of studies was made to obtain a homogeneous and up to date overview on the muscle stem cells applications. Results: In recent years muscle was studied as a good source of adult stem cells that can differentiate into different cell lineages. Muscle stem cells are a heterogeneous population of cells, which demonstrated in vitro a great potential for the regeneration and repair of muscle, bone and cartilage tissue. Among muscle stem cells, satellite stem cells are the most known progenitor cells: they can differentiate in osteoblasts, adipocytes, chondrocytes and myocytes. Conclusions: Although muscle stem cells are a promising field of research, more pre-clinical studies in animal models are still needed to determine the safety and efficiency of the transplant procedures in humans.